Cathedral Caverns. - Snow, Whitney A. (Images of America., 2017)
"In 1952, Jacob "Jay" Gurley explored a Marshall County, Alabama, curiosity known as Bat Cave. Amazed by its stalagmites and sheer enormity, he purchased the site and began transforming it into Cathedral Caverns, a spectacular tourist attraction that eventually became a national natural landmark in 1973 and a state park in 2000. Had it not been for Gurley's hard work and dedication, this cave, a geological treasure of international renown, might have remained a little-known hole in the ground."--Cover.